Cost benefit analysis of wind and hydro power CDM projects in China - Shao, Chunyan (2020)
Renewable Energy (RE) is a solution to solve the Chinese energy problem of increasing demand for energy with high pollution resulting from fossil-fuel energy. The Clean Development Mechanism (CDM) allows China to implement an emission-reduction project, such as wind and hydro power projects, which account for a large share in all renewable energy projects. The aim of the thesis is to apply a cost-benefit analysis to wind and hydro power CDM projects in China. Private Net Benefits (PNB) and Social Net Benefits (SNB) of wind power to hydropower projects under deterministic and stochastic conditions are compared. Monte Carlo simulation is used to analyse the stochastic condition of uncertainty. The results indicate that hydro projects are better than wind power projects, since hydro projects show a high benefit-cost ratio. In addition, the ancillary benefit of citizen’s life saved from using two renewable energy CDM projects is calculated. When taking ancillary benefits into account, the benefits increase substantially. The average level of stochastic estimation of net benefits is close to the deterministic calculation, but stochastic results shows the net benefit for wind and hydro projects can vary dramatically. Furthermore, sensitivity analysis is applied to investigate how a change in discount rates impacts net benefits and the benefit-cost ratio.